Physical activity in working mothers: Running low impacts quality of life. (June 2020) - Limbers, Christine A; McCollum, Christina; Ylitalo, Kelly R; Hebl, Mikki
Objectives: The transition to motherhood is associated with declines in physical activity in women. Working mothers may be particularly at-risk for low levels of physical activity, since they have to balance the competing interests of work and family life, and exercise often takes a backseat to more seemingly pressing concerns. The potential benefits working mothers can experience from physical activity are numerous. The objectives of this study were to evaluate the percentage of working mothers from the United States who met the World Health Organization's and the American College of Sports Medicine's recommended guidelines for weekly physical activity and investigate the associations between physical activity, quality of life, and self-rated work productivity in this sample of working mothers. Methods: Participants were 334 working mothers from the United States (mean age = 35.00 years; standard deviation (SD) = 5.85; 77.8% White) recruited from a Qualtrics research panel. To be eligible to participate in the study, a woman had to be 18 years or older with at least one child aged 5 years or younger, work at least 30 h per week at a job, live with her child(ren) at least 50% of the time, and have a minimum of a bachelor's degree. Participants completed the Godin leisure time exercise questionnaire, the World Health Organization—five well-being index, a single-item indicator of self-rated work productivity, and a demographic questionnaire. Results: Of the working mothers in the sample, 45.5% met the recommended guidelines of at least 150 min of moderate exercise in the past week. Approximately 39% of working mothers reported engaging in no 30-min bouts of strenuous exercise in the past week. Non-white working mothers, working mothers with a higher singular annual income, and working mothers who obtained a higher educational level were more likely to meet the recommended guidelines for physical activity in the past week. Meeting the recommended physical activity guidelines in the past week was associated with better quality of life ( r  = 0.39; p  < 0.001) and self-rated work productivity ( r  = 0.13; p  < 0.05). Only the association between physical activity and quality of life remained significant in a multivariate analysis (standardized beta coefficient = 0.33; p  < 0.001) after controlling for race/ethnicity, maternal singular annual income, and maternal highest level of education. Conclusion: Our findings highlight that working mothers in the United States are a group at risk for low levels of physical activity. Given the great benefits that these women do experience as a function of getting exercise, it is critically important we pay more attention to how individual, organizational, and societal-level interventions might assist them in attaining target levels of physical activity.